2019
DOI: 10.1027/2151-2604/a000378
|View full text |Cite
|
Sign up to set email alerts
|

The Nature and Nurture of HEXACO Personality Trait Differences

Abstract: Abstract. This study was designed to provide detailed estimates of genetic and environmental sources of variance in the HEXACO personality traits. For this purpose, we analyzed data from a German extended twin family study including 573 pairs of twins as well as 208 mothers, 119 fathers, 228 spouses, and 143 offspring of twins. All participants provided self-reports on the HEXACO-60. Extended twin family analyses using structural equation modeling (SEM) yielded that additive and nonadditive genetic influences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…Effects due to shared social background accounted for 16% of the variance in Honesty-Humility, while 10% of the variance was due to spouse-specific interaction. In line with previous studies, however, we found that the transmission of trait similarity from one generation to the next was exclusively genetic with the exception of small variance components due to passive gene-environment correlation (about 2%) for Openness and Extraversion (see Kandler et al, 2019, for more details).…”
Section: Nature and Nurture Of Hexaco Personality Traitssupporting
confidence: 92%
“…Effects due to shared social background accounted for 16% of the variance in Honesty-Humility, while 10% of the variance was due to spouse-specific interaction. In line with previous studies, however, we found that the transmission of trait similarity from one generation to the next was exclusively genetic with the exception of small variance components due to passive gene-environment correlation (about 2%) for Openness and Extraversion (see Kandler et al, 2019, for more details).…”
Section: Nature and Nurture Of Hexaco Personality Traitssupporting
confidence: 92%
“…There was no evidence of an environmental association between parental traits, including anxiety 111 , sociability 110 , and smoking during pregnancy 71 , and offspring personality traits such as sociability and temperament. In addition, an extended twin study found no evidence of environmental transmission or rGE underlying associations between parent and offspring dimensional personality traits 112 . However, two studies observed evocative effects of offspring social behaviours on parenting; adopted offspring’s genetically influenced social behaviours predicted adoptive parent hostility 61 and child-centred parenting 111 .…”
Section: Resultsmentioning
confidence: 94%
“…So whatever personality phenomenon you're studying (see Baumert et al, , for some suggestions), make sure you're measuring all six factors. To take one example, if you'd like to study genetic and environmental influences on personality variation, use the HEXACO factors, as some researchers have recently been doing (Kandler, Lewis, Butković, Vukasović Hlupić, & Bratko, ; Kandler, Richter, & Zapko‐Willmes, ; Lewis & Bates, ). Or if you're interested in ‘network approaches’ to personality, you should start with the HEXACO factors, as has recently been performed by Costantini et al ().…”
Section: Summary Of Objections To Adoption Of Hexaco Model and Responmentioning
confidence: 99%